Agresivitas Pajak Ditinjau dari Karakteristik Perusahaan dan Corporate Social Responsibility - Harjito, Yunus (University of Trunojoyo Madura, 2018)
This study aims to analyze the influence of corporate characteristics and Corporate Social Responsibility to tax aggressiveness. Dependent variable used in this research is tax aggressiveness as measured by effective tax rate. The independent variables in this study are firm characteristics consisting of firm size, leverage, capital intensity. This study also uses Corporate Social Responsibility as an independent variable. The sample in this research is 41 companies with the research period for 5 years (2011-2015) selected by using purposive sampling method. The analysis of data used in this study using multiple linear regression with the hope to obtain a comprehensive picture of the influence of corporate characteristics and Corporate Social Responsibility Aggressiveness of Taxes using SPSS version 21 for Windows. The results showed that firm size and capital intensity significantly affect the aggressiveness of taxes. However, two other variables (leverage and Corporate Social Responsibility) alleged to affect tax aggressiveness but not proven to affect the aggressiveness of the Tax.